On variety and tolerance - Snyman, Gerrie 19XX- (Old Testament essays, 2016)
Old Testament Essays (New Series) is an instrument through which scholars can publish their research in the field of the Old Testament or Hebrew Bible. Its readers are members of the Old Testament Society of South Africa, scholars in Africa, and the rest of the world interested in the Old Testament in general as well as in (South) African biblical scholarship. The primary aim of the journal is to propagate the study of the Old Testament in (South) Africa from various points of view as well as within numerous fields related to the study of the Old Testament.